Environmental Taxation and Redistribution Concerns - Rafael Aigner (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
How is the optimal level of Pigouvian taxation influenced by distributive concerns? With second-best instruments, a higher level of income redistribution calls for a lower level of Pigouvian taxation. More redistribution implies higher distortions from income taxation. Pigouvian tax revenues become more valuable and the optimal level of environmental taxation decreases. With first-best in- struments, however, the relation between levels of redistribution and Pigouvian taxation is reversed. So second-best Pigouvian taxes are very different from their first-best counterpart - despite apparently identical first order conditions.
Keywords: H21; H23; D62; 330